Bridging the Research/Teaching Divide with DAH and SoTL-AH. (3rd April 2019) - Spivey, Virginia B.; McGarry, Renee
Abstract : This paper explores the potential for rigorous pedagogical scholarship to complement developments in digital art history (DAH). In addition to introducing ideas and methods that characterize scholarship of teaching and learning (SoTL) in higher education, we focus on two major themes: how digital tools and techniques can support robust scholarship of teaching and learning in art history (SoTL-AH) and ways that SoTL-AH can be used to evaluate and demonstrate the impact of DAH projects in the classroom and the public realm. Our goal is to encourage greater exchange between these two emerging fields that can together advance art historical study.